PENGGUNAAN METODE KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VA SDN 021 TANJUNG PALAS KECAMATAN DUMAI TIMUR - Sejati ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low result of fifth grade students learn math SDN 021Tanjung Palas. The low learning outcomes due to: (a) students find it difficult to understandthe elements and properties of geometrical abstract; (B) how to deliver materials that arelacking attract students to understand the material I teach, always using methods lectures,discussion, assignments. This study aims to improve the learning outcomes of mathematicsthrough STAD cooperative method. This research is a class act, carried out by two cycles.The study states that hasila learning has increased, this is evidenced by the base score is thenumber of students who completed 16 students (44.4%), in the first cycle is the number ofstudents who pass the 25 students (69.4%). And the second cycle is the number of studentswho pass the 32 students (88.9%).